QUALITY OF LIFE - Bortesi Longhi, Luis (2011)
The issue of quality of life contains the core purpose and natural that everyone pursues instinctively sometimes and in some other cases with clear consciousness and so does the whole society which proposes objectives and goals for better living. Governments, meanwhile, also have final objective or the purpose of achieving uncompromising “general welfare” for their people, but in this context requires a previous reflection, that is premised, to examine in detail such an important concept and so important what the real content and dimension about quality of life. Obviously not all the factors that concur in determining the level of satisfaction are material but on the contrary, although the progressive realization of the modern world and technology seem to ignore it, the main components of quality of life, qualitative by definition, not derived flow of income or the amount consumed as live better means growing demands and virtues that transcend the realm of quantity.